Implementation of Community-Based Ecotourism through Waste Management: The Study Case of Sukunan Tourism Village, Yogyakarta, Indonesia - Ayu Apriliyanti; Filippo Randelli (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2020)
The research aims to investigate the transformation process required within an Indonesian village in order to overcome huge waste management problems by enhancing the ecotourism sector, as well as to analyze the innovations introduced to improve the environmental quality standards of the local inhabitants. It presents some findings from a field study in Sukunan Village, Yogyakarta (Indonesia), used as a case study to delve deeper into several issues related to ecotourism development via innovative waste management systems. To investigate the ecotourism phenomenon in this context, the research employs a qualitative approach, conducting in-depth interviews with several key informants who are currently residing in the village. This study demonstrates that the development of ecotourism through waste management has a positive impact on the village’s social, economic, and environmental life, reevaluating a sub-urban context within an area that is unfortunately known for being one of the most polluted in the world.